Anatomical, morphological and chemical properties of Tobacco stalk (Nicotiana tabacum L.) - Vahid Safdari (Regional Information Center for Science and Technology (RICeST), 2012)
Tobacco (Nicotiana tabacum) is one of the non-wood species and its stalks are the main crop after harvesting  which can be used in composite board and paper industry. For better use of this non-wood fibrous raw material, the evaluation of anatomical, morphological and chemical components are necessary. Tobacco stalks "Coker"cultivar 347 which is widely planted in Gilan province of Iran were randomly sampled. Anatomical properties (cross, tangential and radial sections) and morphological properties (fiber length, fiber diameter, and cell wall thickness) were measured and the indices and ratio of the fibers including: slenderness index, runkel index, flexibility ratio in three heights of stem (5%, 50% and 75%) were calculated. The Chemical components including: Cellulose, lignin, ash, alpha cellulose and hemicellulose of stem with bark and without bark were recorded according to related standards and the results were ststistically analyzed. Results showed that the chemical components of the tobacco stalk were desirable but the index of L/D of fibers were lower than many non-woods and hardwoods. Therefore, it is assumed that the paper produced from tobacco stalks do have suitable tear strength. The runkel index (2 cell wall thickness / fiber diameter) is close to hardwoods and many non-woods, Therefore, it is presumed that paper have appropriate tensile, burst and folding strength. It is predicted that tobacco stalks combined with softwoods with long fibers can produce good quality paper.